2010
DOI: 10.1103/physrevlett.105.057002
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Terahertz Emission of Intrinsic Josephson Junction Stacks in the Hot Spot Regime

Abstract: We report on THz emission measurements and low temperature scanning laser imaging of Bi2Sr2CaCu2O8 intrinsic Josephson junction stacks. Coherent emission is observed at large dc input power, where a hot spot and a standing wave, formed in the "cold" part of the stack, coexist. By changing bias current and bath temperature, the emission frequency can be varied by more than 40%; the variation matches the Josephson-frequency variation with voltage. The linewidth of radiation is much smaller than expected from a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
138
6
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(158 citation statements)
references
References 43 publications
13
138
6
1
Order By: Relevance
“…Due to strong extraction of Joule heat (the self-heating) the temperature of junctions in the center of the line can exceed the temperature at ends as much as 1.5 times that can lead to the formation of the "hot spot" in the center of the line, whereas at the same time junctions at ends of the line radiate coherently. Thus, we showed that three particularities noted in experiments [2][3][4][6][7][8], namely the self-induced resonant steps on I-V characteristics, strong coherent emission at these steps and the appearance of "hot spots" have the same origin that is the resonance behavior of the system at certain bias currents. …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Due to strong extraction of Joule heat (the self-heating) the temperature of junctions in the center of the line can exceed the temperature at ends as much as 1.5 times that can lead to the formation of the "hot spot" in the center of the line, whereas at the same time junctions at ends of the line radiate coherently. Thus, we showed that three particularities noted in experiments [2][3][4][6][7][8], namely the self-induced resonant steps on I-V characteristics, strong coherent emission at these steps and the appearance of "hot spots" have the same origin that is the resonance behavior of the system at certain bias currents. …”
Section: Discussionmentioning
confidence: 95%
“…The detail calculations can be made with the use of the proposed model. Note that for the description of the experiments [2][3][4][6][7][8] with the given width of the sample it is necessary to calculate distributions of voltages and currents also along the y-axis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabrication of clear rectangular mesas with sharp edges [9] and emission characteristics of THz emitting mesas were reported. Hot spot is another important theme and is under intense investigation [10].…”
Section: Introductionmentioning
confidence: 99%
“…The successful observations of coherent emission from cuprate superconductors renew the interests in understanding the synchronization of arrays of Josephson junctions [11][12][13][14][15][16][17] . Cuprate superconductors, such as Bi 2 Sr 2 CaCu 2 O 8+δ (BSCCO), are a natural realization of a stack of Josephson junctions of atomic thickness 18,19 , known as intrinsic Josephson junctions (IJJs).…”
Section: Introductionmentioning
confidence: 99%